Commitment, attitude and behavioural changes of the community towards a waste segregation program: a case study of Malaysia - Syed Ismail, Sharifah Norkhadijah; Hashim, Hajar Mariah; Rasdi, Irniza; Zainal Abidin, Emilia (WIT Press, 2014)
The rate of waste segregation is poor in Malaysia where only 5% of waste is segregated and recycled. This cross-sectional study was conducted at Taman Sri Andalas, Serdang Jaya Selangor to determine factors that are associated with the participation of the public in a waste segregation program and to determine the reduction of waste from the waste segregation activity implemented in this study. A total of 69 households were arbitrarily selected across streets to participate in this study. Two types of bins (i.e. recycled and food waste) were provided to each participating household and the weights of the waste were measured at two different time intervals. The behavioural changes of respondents were assessed based on the Theory of Planned Behaviour. The volume of waste segregated has increased significantly, from 9.4% to 10.6% while 13.3% of the community waste is food waste that could be used as compost. In total, the volume of waste designated for the landfill has decreased from 100% to 76.2% in the span of three weeks. Nine behavioural factors show significant positive changes between the start and the end of the program. The waste segregation program that was conducted has resulted in behavioural changes of households towards waste segregation activity.